2020
DOI: 10.1016/j.actaastro.2020.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of shock-wave diffraction over double cylindrical wedges. Part II: Vorticity generation

Abstract: The unsteady aspect of turbulent flow structures generated by a shock-wave diffraction over double cylindrical wedges, with initial diffracting angle of ∘ 75 , are numerically investigated by means of two-dimensional highfidelity numerical simulation. Different incident-shock-Mach numbers, ranging from transonic to supersonic regimes, are considered. Unlike previous studies where only the total vorticity production is evaluated, the current paper offers more insights into the spatio-temporal behavior of the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Whereas, in DTP, the first Mach Stem becomes the incident shock for the second detached reflection. Brahmi et al [16] showed that for low Mach numbers, viscosity plays an important role in the diffusion of the vorticity as compared to the baroclinic term, while this is the opposite for higher Mach number cases. The unsteady separation behind diffracted shock over convex curved walls was experimentally and numerically investigated at large lengths and time scales by Law et al [17].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, in DTP, the first Mach Stem becomes the incident shock for the second detached reflection. Brahmi et al [16] showed that for low Mach numbers, viscosity plays an important role in the diffusion of the vorticity as compared to the baroclinic term, while this is the opposite for higher Mach number cases. The unsteady separation behind diffracted shock over convex curved walls was experimentally and numerically investigated at large lengths and time scales by Law et al [17].…”
Section: Introductionmentioning
confidence: 99%